Experimental Models of SARS-COV-2 Infection in the Central Nervous System. (7th May 2022) - Paoletti, Anna Maria; Melilli, Maria Grazia; Vecchio, Immacolata
Coronavirus disease 2019 (COVID-19) has raised serious concerns worldwide due to its great impact on human health and forced scientists racing to find effective therapies to control the infection and a vaccine for the virus. To this end, intense research efforts have focused on understanding the viral biology of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for COVID-19. The ever-expanding list of cases, reporting clinical neurological complications in COVID-19 patients, strongly suggests the possibility of the virus invading the nervous system. The pathophysiological processes responsible for the neurological impact of COVID-19 are not fully understood. Some neurodegenerative disorders sometimes take more than a decade to manifest, so the long-term pathophysiological outcomes of SARS-CoV-2 neurotropism should be regarded as a challenge for researchers in this field. There is no documentation on the long-term impact of SARS-CoV-2 on the human central nervous system (CNS). Most of the data relating to neurological damage during SARS-CoV-2 infection have yet to be established experimentally. The purpose of this review is to describe the knowledge gained, from experimental models, to date, on the mechanisms of neuronal invasion and the effects produced by infection. The hope is that, once the processes are understood, therapies can be implemented to limit the damage produced. Long-term monitoring and the use of appropriate and effective therapies could reduce the severity of symptoms and improve quality of life of the most severely affected patients, with a special focus on those have required hospital care and assisted respiration.